Brain Disorders Related to The Learning Process - Zulpandri; Ronaldi; Dasrizal Dahlan; Ahmad Lahmi; Rosniati Hakim; Kani Ulger (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: The purpose of this study is to deeply understand the role of the brain in the learning process, as well as identify various types of brain disorders that impact students' cognitive abilities. In addition, this study also aims to examine how certain neurological disorders, such as dyslexia, Minimal Brain Dysfunction, dyscalculia, and attention deficit hyperactivity disorder, affect students' academic performance and daily life. This research is expected to provide a neuroscientific perspective in designing learning strategies that are more inclusive and responsive to specific learning needs. Theoretical framework: The theoretical framework is based on the neuroscience approach of education, specifically the concepts of brain plasticity, the function of the hemispheres, and the role of the central nervous system in learning. Literature review: The literature review covers brain development and function, as well as various disorders such as dyslexia, DMO, ADHD, and dyscalculia, which have a direct impact on learning ability. Methods: This study uses a descriptive qualitative method with a literature review approach. The data was analyzed using content analysis from various scientific literature sources. Results: The results of the study show that brain function has a very important role in supporting the learning process. Connections between neurons are formed through experience and appropriate stimuli, while disturbances in brain structure or function can cause various difficulties in the learning process. Disorders such as Minimal Brain Dysfunction, dyslexia, dyscalculia, and attention deficit hyperactivity disorder significantly affect concentration, memory, and the ability to read, write, and count in school-age children. In addition, the dominance of left-brain or right-brain function also affects a person's learning style, so learning strategies need to be adjusted to the cognitive tendencies of each student. Implications: The results of this study encourage the importance of understanding neuroscience in education so that learning strategies can be adjusted to the neurological condition of students. Novelty: The novelty of this research lies in the integration of neuroscience and Islamic educational approaches in understanding and dealing with learning disorders holistically and empathically.